Isolation of Endophytic Fungi QPS 05 from Quercus phillyraeoides A. Gray and Its Potential for Î±-Glucosidase Inhibitory Activity - Anastasia Wheni Indrianingsih; Amalia Indah Prihantini; Sanro Tachibana (Jurnal Kimia Terapan Indonesia, 2018)
AbstractEndophytic fungi are the microorganisms that spend all or part of their life cycles within plant tissue without causing harmful effects on the plant. In this study, 14 endophytic fungus from Quercus phillyraeoides A. Gray were isolated. Alternaria sp. QPS 05, an endophytic fungi which was isolated from the stem of Q. phillyraeoides A. Gray showed the highest Î±-glucosidase inhibitory activity. Further separation of ethyl acetate extract from the fungus led to the isolation of active substance from hexane-soluble fraction which give fatty acids mixture consist of palmitic acid, oleic acid, linoleic acid and linolenic acid (1) strong inhibitory activity against Î±-glucosidase. Isolated fatty acids (1) had inhibitory concentration (IC50) values against Saccharomyces cerevisiae was 12.10 Î¼g/mL. The results of the present study showed that endophytic fungus from Alternaria sp. QPS 05 potentially contained a rich source of natural antidiabetic medicine.